Penerapan Brisk Walking Exercise terhadap Penurunan Tekanan Darah pada Penderita Hipertensi di Jakarta - Adillah, M Luthfi; Sari, Putri Permata; Isnayati, Isnayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of brisk walking exercise in reducing blood pressure in hypertensive patients. This type of research uses descriptive case study research methods. The subject of this research was 4 respondents. Data collection techniques were carried out by measuring blood pressure before the intervention was given at all and when the intervention was carried out, blood pressure was measured before and after the intervention. This research was conducted 3 days a week with a frequency of 15-30 minutes. The results of the study showed that brisk walking was able to reduce the blood pressure of hypertension sufferers with an average decrease in systolic pressure of 3.95 mmHg and an average diastolic pressure of 3.3 mmHg. In conclusion, the application of fast walking techniques is a non-pharmacological method that can control blood pressure in hypertensive patients because it has an effect on reducing blood pressure. Key Words: Hypertension; Blood Pressure; Brisk Walking Exercise